Clinical outcomes at 2 years of the Absorb bioresorbable vascular scaffold versus the Xience drug‐eluting metallic stent in patients presenting with acute coronary syndrome versus stable coronary disease—AIDA trial substudy. Issue 1 (9th April 2019) - Tijssen, Ruben Y.G.; van der Schaaf, Rene J.; Kraak, Robin P.; Vink, Maarten A.; Hofma, Sjoerd H.; Arkenbout, E. Karin; Weevers, Auke P.J.D.; Kerkmeijer, Laura S.M.; Onuma, Yoshinobu; Serruys, Patrick W.; Beijk, Marcel A.M.; Koch, Karel T.; et al.
Abstract: Background: Patients with acute coronary syndrome (ACS) might represent a specific subgroup, in which bioresorbable scaffold implantation in percutaneous coronary intervention (PCI), might lead to better outcomes when compared to conventional treatment with metallic drug eluting stents. In this prespecified subgroup analysis of the Amsterdam Investigator‐Initiated Absorb Strategy All‐Comers (AIDA) trial, we evaluated the clinical outcomes of Absorb bioresorbable vascular scaffold (BVS) versus Xience everolimus eluting stent (EES) treated patients presenting either with or without ACS. Methods and results: We classified AIDA patients on the basis of clinical presentation of ACS or of no‐ACS. The rate of the 2‐year primary endpoint of target vessel failure (TVF) was similar after treatment with Absorb BVS or Xience EES in ACS patients (10.2% versus 9.0% respectively; P  = 0.49) and in no‐ACS patients (11.7% versus 10.7%, respectively; P  = 0.67) Definite or probable device thrombosis occurred more frequently with Absorb BVS compared to Xience EES in ACS patients (4.3% versus 1.7%, respectively, P  = 0.03) as well as in no‐ACS patients (2.4% versus 0.2%, respectively; P  = 0.002). There were no statistically significant interactions between clinical presentation and randomized device modality for TVF ( P  = 0.80) and for the endpoint of definite or probable device thrombosis ( P  = 0.17). Conclusion: In the AIDA trial, the 2‐year outcomes of PCI with Absorb BVS versus Xience EES were consistent in ACS and no‐ACS patients: similar rates for TVF and consistently higher rates of definite or probable stent thrombosis under Absorb BVS versus Xience EES. There were no statistically significant interactions between clinical presentation and randomized device modality.